Morphometric Study of the Maximum and Curved Vertical Diameters of the Head of the Humerus in Bangladeshi Population - Haque, Shah Md Atiqul; Mehataz, Tasnova; Biswas, Tithi Rani; Latif, Md Safat; Khanam, Sultana Razia (Community Based Medical Journal, 2025)
The head of the humerus bone articulates with the glenoid cavity of the scapula to form the glenohumeral joint. Glenohumeral joint is a multi-axial joint, which is one of the most mobile and unstable joints in human body. Morphometric analysis of the head of the humerus is important to understanding of shoulder joint’s stability and functions. A cross-sectional, descriptive study was conducted in the Department of Anatomy, Mymensingh Medical College, Bangladesh, from July 2021 to June 2022, to determine the maximum and curved vertical diameters of the humeral head in a Bangladeshi population. We collected 100 dry adult humerus bones (right sided 43 and left sided 57) through the non-random, purposive sampling technique. Damaged, unossified or fractured bones were excluded. A digital slide calipers was used to measure the maximum vertical diameter of the head of the humerus, while its curved vertical diameter was measured by flexible measuring tape. The mean maximum vertical diameters of the head of the right and left humeri were found 41.965±3.425 mm and 41.548±3.647 mm respectively. The mean curved vertical diameters of the head of the right and left humeri were found 59.093±5.706 mm and 57.403±5.506 mm respectively. We expect that the findings of our study will be helpful for clinical anatomists, orthopaedic surgeons, radiologists, anthropologists, and forensic experts. CBMJ 2025 July: vol. 14 no. 02 P:93-97